Effect of Freeze-Thaw Cycles on Mechanical Properties of an Embankment Clay: Laboratory Tests and Model Evaluations - Zhang, Anshun; Zhang, Junhui; Peng, Junhui; Huang, Chao; Zhou, Chao (Frontiers in Earth Science, 2022)
Freeze-thaw (FT) cycling is a crucial issue in seasonal frozen regions and it will influence the mechanical properties of soils which must be strictly concerned for embankment engineering. This study conducted a series of unconsolidated and undrained triaxial tests under various closed-system FT cycles to investigate the mechanical properties of a typical embankment clay from China. Results indicated that the stress-strain curves changed from strain hardening or stabilization to softening during FT cycles. The elastic modulus was obviously weakened by FT cycles and declined sharply after the first FT action. The failure strength gradually reduced with the accumulation of FT cycles and eventually tended to be stable when the FT cycles achieved 10, and the attenuation range was approximately 6% to 22% compared with the condition before FT cycles. Moreover, a phenomenological model on the failure strength was established by results of the tested clay in this study and validated to be robust through multiple sets of different clays data from other published literatures. Based on it, combined with the Mohr stress circle equation and envelope theory, an innovative method for rapidly obtaining the shear strength was proposed. The ensuing discoveries were that the cohesion damaged in the course of the first few FT cycles and then kept basically constant undergone 10 cycles, while the internal friction angle was not sensitive to FT cycles. The normalized empirical formula was deduced and can simultaneously apply to the strain hardening, stabilization and softening curves given that the effect of FT cycles.